2022
DOI: 10.1098/rsbl.2022.0052
|View full text |Cite
|
Sign up to set email alerts
|

Increased signal complexity is associated with increased mating success

Abstract: The evolution of complex signals has often been explored by testing multiple functional hypotheses regarding how independent signal components provide selective benefits to offset the costs of their production. In the present study, we take a different approach by exploring the function of complexity per se . We test the hypothesis that increased vibratory signal complexity—based on both proportional and temporal patterning—provides selective benefits to courting male Schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…This finding is consistent with the idea of multifarious selection providing more axes for ecological or phenotypic divergence among species, and can eventually lead to speciation (Nosil et al, 2009). However, recent work in wolf spiders has revealed that signal complexity per se can be a direct target of sexual selection (Choi et al, 2022). Another possibility in kingfishers is that body size is driving the evolution of plumage complexity, as signal complexity has been shown to decrease with body size in iguanian lizards (Ord and Blumstein, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the idea of multifarious selection providing more axes for ecological or phenotypic divergence among species, and can eventually lead to speciation (Nosil et al, 2009). However, recent work in wolf spiders has revealed that signal complexity per se can be a direct target of sexual selection (Choi et al, 2022). Another possibility in kingfishers is that body size is driving the evolution of plumage complexity, as signal complexity has been shown to decrease with body size in iguanian lizards (Ord and Blumstein, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis may be supported by the lack of signi cant effects of male body condition (i.e. body mass) on vibratory signal complexity (Choi et al, 2022). However, to validate this hypothesis, further studies in controlled laboratory environments are necessary to investigate the variation in female preference and male signaling behavior across the density of conspeci c and heterospeci c signals.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the realistic effects of general In addition to the three signal characteristics mentioned previously (bout duration, dominant frequency, peak rate), we also explored the effects of variation in the abundance and diversity of general noise (Obj.IIIa) and conspeci c/heterospeci c signals (Obj.IIIb) on the structural complexity of detected courtship signals of S. stridulans. We focused on complexity in S. stridulans speci cally, as prior research has demonstrated an in uence of male vibratory signal complexity on mating success (Choi et al, 2022).…”
Section: Objective III -Examine Behavioral Plasticity In the Courtshi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The visual system is essential for insects to collect abundant information from their surroundings and respond appropriately, including making choices among alternative behaviors, foraging, and mating [ 1 4 ]. Generally, the spectral sensitivity of photoreceptor cells is determined by the photopigment, a complex of chromophore and opsin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%